The centrosome and the DNA damage induced checkpoint. - Fletcher, L; Muschel, R (2006)
The centrosome, the microtubule-organizing center of the cell, acts as a localization point, where signaling molecules are able to interact. Many kinases and phosphatases critical for regulation of DNA damage signaling pathways localize to the centrosome. This review will discuss the possible involvement of the centrosome in mediating DNA damage checkpoint control, in particular the effect of DNA damage signaling pathways involved in initiation or maintenance of cell cycle arrest on the centrosome. The mechanisms that lead to centrosome abnormalities such as centrosome hyperamplification and multipolarity in response to DNA damage will also be addressed.